PENGEMBANGAN KAMUS SAKU ARAB-INDONESIA UNTUK MENINGKATKAN KETRAMPILAN MEMBACA SISWA KELAS VIII DI PESANTREN ROUDHOTUL QUR’AN AN-NOER - Rina Dian Rahmawati; Ima Liana (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2021)
The purpose of this study is to develop an Arabic-Indonesian pocket dictionary to improve reading vocabulary and to determine the feasibility and effectiveness of learning media in the form of a pocket dictionary. This research is an R&D research that adopts the development of ADDIE. The subjects in this study were class VIII students of the Roudhotul Qur'an An-noer Islamic Boarding School, totaling 15 students and data collection used in the form of media expert questionnaires, material expert questionnaires, student response questionnaires, pre-test, and post-test. The types of data analyzed produce qualitative and quantitative data with assessment categories to determine product feasibility. The results of this study are: 1) a learning media in the form of an Arabic-Indonesian pocket dictionary has been developed. 2) the feasibility of the pocket dictionary learning media that has been developed is very feasible with an almost comprehensive score reaching a value of 4 (quite valid) based on the assessment of material experts and a very decent score almost completely reaching a value of 4 (quite valid) based on the assessment of media experts. 3) the effectiveness of learning media in the form of pocket dictionaries is very effective, seen from the average pre-test score obtained by students compared to the post-test score, with an average pre-test score of 49 and an average post-test score of 80.